Three predictive policing approaches in Spain: VIOGÉN, RISCANVI and VERIPOL: Assessment from a human rights perspective (2024)
What is the predictive accuracy and effectiveness of algorithms designed for crime prevention purposes? Are they sufficiently transparent? Are there any inherent biases? This report presents an analysis of three algorithmic tools used by the Spanish administration for predictive analytics in the police and prison sector (VioGén, RisCanvi and VeriPol, the latter of which employs artificial intelligence). The aim is to evaluate the functioning of these three algorithmic systems, particularly in terms of their adherence to fundamental rights. The study employs a mixed-methods approach, integrating quantitative and qualitative techniques. It has been carried out by professors at the Universitat de València and the Universitat Politècnica de València, experts in a range of legal fields (criminal, administrative and constitutional law), as well as in statistics and mathematics. The principal findings of the report are as follows: 1) It analyses the predictive accuracy of the three systems and their effectiveness in achieving their intended goal (crime reduction); 2) assesses their degree of transparency for the general public and for the people directly affected by their use; 3) identifies and discusses possible biases; 4) analyses whether they comply with the current European and Spanish legal framework, with particular attention to the protection of personal data and the regulations governing the use of automated decision-making systems. The study discusses whether the costs incurred in terms of fundamental rights exceed what is necessary and/or proportionate to the actual or likely benefits in terms of crime prevention. Furthermore, it underscores the importance of enhanced transparency to facilitate the necessary public debate on the instruments employed by public authorities, such as the three systems under analysis, which may result in limitations on fundamental rights.¿Cuál es la precisión predictiva y la eficacia de los algoritmos diseñados con fines de prevención de la delincuencia? ¿Son suficientemente transparentes? ¿Existen sesgos inherentes? Para responder a estas cuestiones se presenta un estudio de tres herramientas algorítmicas utilizadas por la Administración española para el análisis predictivo en el sector policial y penitenciario (VioGén, RisCanvi y VeriPol, esta última de inteligencia artificial). Con ello se pretende evaluar su funcionamiento, en particular en términos de su adhesión a los derechos fundamentales. El estudio emplea un enfoque de métodos mixtos, integrando técnicas cuantitativas y cualitativas. Ha sido realizado por profesores de la Universitat de València y de la Universitat Politècnica de València, expertos en diversos campos jurídicos (derecho penal, administrativo y constitucional), así como en estadística y matemáticas. Los principales objetivos son: 1) analizar la precisión predictiva de los tres sistemas y su eficacia en la consecución de la finalidad perseguida (reducción de la delincuencia); 2) valorar su grado de transparencia para el público en general y para las personas directamente afectadas por su uso; 3) identificar y discutir posibles sesgos; 4) analizar si cumplen con el marco legal europeo y español vigente, con especial atención a la protección de datos personales y a la normativa que regula el uso de sistemas automatizados de toma de decisiones. Así mismo, se analiza si los costes en términos de derechos fundamentales exceden lo necesario o son proporcionales a los beneficios reales o probables en términos de prevención de la delincuencia. Además, se subraya la importancia de la transparencia para facilitar el necesario debate público sobre los instrumentos empleados por las autoridades públicas, como los tres sistemas analizados, que pueden dar lugar a limitaciones de los derechos fundamentales.
Keywords: penal; derechos humanos; criminología; policía